Nephrolithiasis and Nephrocalcinosis in Childhood—Risk Factor-Related Current and Future Treatment Options - Weigert, Alexander; Hoppe, Bernd (Frontiers in Pediatrics, 2018)
Nephrolithiasis (NL), Urolithiasis (UL) and Nephrocalcinosis (NC) have become common causes of hospitalization and referral to pediatric outpatient clinics. It is of utmost importance to start with diagnostic evaluation directly after the first passage of a kidney stone, or if nephrocalcinosis is diagnosed, in each pediatric patient. This is necessary, as in about 80% of children a metabolic reason for stone disease is detected. Current treatment options are scarce and mainly include general measures like an increased fluid intake or elevating the solubility of a lithogenic substance. According to the given lithogenic risk factor(s), specific treatment options are available and are being summarized in this review. Furthermore, an outlook on potential future treatment options, including innovative strategies like mRNA based- or recombinant enzyme substitution therapy, is given.